LINGUISTIC FEATURES OF BUSINESS ENGLISH DISCOURSE THESAURUS - Nataliia V. Zinukova (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
In this article the features of Business English discourse thesaurus have been analyzed. Knowledge of institutional Business English discourse, which is a sign of translators’ activity, is one of the mandatory qualification characteristics of the translator’s language personality in general and the interpreter in particular. Taking into account the specifics of the translator’s professional activity, the peculiarities of Business English discourse thesaurus, including words in their direct nominative meaning, and words with terminological meaning, are determined as well as the features of word-forming model (affixation, word-formation, conversion, reduction, synonymy), frequently used phraseological units that carry certain information about national peculiarities of the worldview of native speakers; metaphorical units and emphatic constructions. Based on the continuous sampling method (to identify lexical units of institutional Business English discourse for further analysis), the method of dictionary definitions (to study the semantics of lexical units), contrastive method (to establish common and distinctive features for translation) and descriptive method (to identify and systematization of features and difficulties of translation of lexical units of Business English discourse) the features of functioning of Business English discourse thesaurus are analyzed. The peculiarities of business discourse include stability and standardization due to the scope of its application between people, institutions and states. Since business discourse is characterized by strict accuracy, objectivity, specificity, conciseness, lack of imagery and emotionality, the choice of language means for it will be determined by the same features, because in the business style, the content should exclude ambiguity and the possibility of ambiguity. Despite the differences in content and variety of genres, business discourse in general is characterized by a number of common features, in particular: brevity, compactness of presentation, economical use of language; standard arrangement of material, often mandatory to use the inherent clichés of this style; extensive use of terminology, nomenclature names, the presence of a special layer of vocabulary and phraseology, the introduction of complex words and abbreviations. One main characteristic feature of the lexical composition of business discourse are terms. In addition to terms, there are common and special kinds of vocabulary (words and phrases that do not have the property of the term to identify concepts and objects in a particular field, but used exclusively in this field of communication) at the lexical level in each of the types of institutional Business English discourse. Special vocabulary can include both word-derived words and a number of commonly used words that function in the fixed phrases, thus being considered specialized. Another feature of Business English discourse, manifested at the morphological level, is the wordformation model of business language based on business terminology, which reveals four main ways of morphological word formation: affixation, word formation, conversion, abbreviations (lexical and graphic) and synonymy as a semantic phenomenon. Business English discourse, both oral and written, is characterized by a fairly high degree of idiomaticity, which really is a difficulty for translators working in the foreign economic field. Linguistic material of modern Business English discourse, which distinguishes it from other types of discourses, are precedent metaphors (precedent names, precedent utterances, precedent texts, precedent phenomena). They add a lively and figurative character to the business language, not depriving business discourse of accuracy, but increasing its pragmatic influence, due to their authenticity and high associative potential. In Business English oral discourse emphatic constructions (emphasis often occurs in the form of an inversion or emphatic construction with the previous It) are widely used to emphasize and give an emotionally expressive character to the utterance. Inversion can be conveyed syntactically (sentence reconstruction) and lexically (using various reinforcing words, such as “only”, “very”, “enough”, “too much”), grammatical constructions with It, which stands at the beginning of the sentence, constructions with the so-called Condensed Relative with the relative pronoun what in contracted subject or additional sentences. The most common cases are the presence in sentences of negative emphatic constructions with “no” before nouns. It is established that the success of each specific situation of intercultural business communication directly depends on the translator’s ability to correctly interpret the meaning of expression in the process of his professional activity.